Effects of 12-Week Exercise Program on Enzyme Activity of Serum Matrix Metalloproteinase-9 and Tissue Inhibitor of Metalloproteinase-1 in Female Patients with Postmenopausal Osteoporosis: A Randomized Control Study. (30th January 2020) - Filipović, Tamara; Gopčević, Kristina; Dimitrijević, Sanja; Hrković, Marija; Backović, Ana; Lazović, Milica
Abstract : Background . Osteoporosis is a disease characterized by decreased bone density and destruction of bone microarchitecture. Indicators for altered bone homeostasis are changes in the serum level of matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs). The purpose of the current study was to evaluate the effect of a 12-week exercise program on enzyme activity of serum MMP-9 and TIMP-1 in postmenopausal osteoporotic patients. Materials and methods . Participants were randomized in two groups: exercise (EG) ( N  = 37) and control (CG) ( N  = 31). The exercise group completed a 12-week supervised exercise program, while the control group did not take part in any physical activity. Enzyme activities of serum MMP-9 and TIMP-1 were detected by gelatin zymography and ELISA in both groups, respectively. Results . Significant differences between pretreatment and posttreatment enzyme activities of serum MMP-9 (p = 0.009 ), TIMP-1 (p ≤ 0.001 ), and MMP-9/TIMP-1 ratio (p ≤ 0.001 ) were detected in the exercise group. Exercises decreased the activity of serum MMP-9 and increased the activity of TIMP-1, while the enzyme activities of MMP-9 (0.583) and TIMP-1 (0.210) have not been significantly changed in CG. Patients from the exercise group had better treatment. Conclusion . Our results suggest that a 12-week exercise program has an influence on enzyme activity of serum MMP-9, revealing a possible role of MMPs in initiating training-specific adaptation. Although measurements of circulating MMP-9 and TIMP-1 allowed us to detect effects of exercise, as of today, they have no real role in the diagnosis of osteoporosis and/or follow-up of osteoporotic patient's response to treatment. MMP-9 might be used as an important prognostic marker for the evaluation of patient's response to exercise. Larger-randomized controlled studies need to be performed to expand this area of knowledge. This trial is registered with trial registration number: NCT03816449 ).